Improving Students’ Listening, Speaking, and Vocabulary Mastery through Conversation-Based Communicative Language Teaching at Yayasan Almadania Kampar Riau - Zaiful Zuhri; Amiatun Nuryana (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
This study aims to examine the implementation of Communicative Language Teaching (CLT) through conversation-based activities to support students’ listening ability, speaking ability, and vocabulary mastery. The research was motivated by students’ challenges in understanding spoken English and expressing ideas orally due to conventional teacher-centered methods. A qualitative descriptive design was employed, involving one English teacher and twenty eighth-grade students at Yayasan Almadania Kampar Riau during the 2025/2026 academic year. Data were collected through classroom observation, interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicated positive changes in the classroom environment, where conversation-based activities—such as group discussions and pair work—appeared to foster higher student engagement and confidence. Observations and interview data revealed perceived improvements in students' ability to follow oral instructions, their fluency during interactions, and a more varied use of vocabulary in context. The study concludes that integrating conversation within a CLT framework serves as a beneficial approach for developing integrated language skills in EFL classrooms by providing meaningful opportunities for social interaction